ANALISIS BMC, SOCIAL BUSINESS CANVAS, DAN CUSTOMER DEVELOPMENT PADA STARTUP EDUKASI BERBASIS SOSIAL - Hanifah, Salma; Handrito, Radityo Putro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Many cases of sexual violence in Indonesia has recently drawn public attention. Teaching young people about sexuality is one way to lessen the incidence of sexual violence. The first Islamic-based sexuality education curriculum and module are created by Taulebih, an Indonesian social startup. Taulebih has been in operation for over a year, but it has never developed a thorough business plan. The operational actions that occurred within Taulebih between June 2022 and January 2023 are mapped using Business Model Canvas and Social Business Canvas analysis in this descriptive qualitative study. The outcomes of Taulebih's BMC analysis were then put to the test using a customer development procedure that resulted in the creation of a customer archetype. The result are six customer archetypes which leads to the conclusion that Taulebih targets a niche market where its products are well recognized to general customers but are tailored to meet more specialized needs by incorporating Islamic principles into the curriculum and lesson plans.